A Cross Sectional Study on Serum Follicle Stimulating Hormone and Luteinizing Hormone in Patients with Anovulatory Disorders with Primary Infertility - Nida, Maryam Ahmad Qureshi, Humera Usman, Atika Akram, Samina Rehan Khan, Noureen Jawad, Muhammad Fahad Bhutta, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Infertility is defined as the inability to conceive after one to two years of unprotected intercourse. It is of two types: primary infertility and secondary infertility 5On the basis of etiopathology infertility is divided into five groups: unexplained (28%), male factor (24%), ovarian dysfunction (21%), tubal factor (14%) and others (13%). Luteinizing hormone (LH) and follicle-stimulating hormone (FSH) are integral parts of the neural and endocrine interchange between the hypothalamus, pituitary, and gonads that control steroid hormone synthesis and gamete production. Method: The design of this study was a Cross sectional study design. The study was conducted in Shifa International Hospital Islamabad and the duration of this study were from May 2022 to Nov 2022 for the duration of six months. Results: A total of 143 female patients presenting with an ovulatory cycle with primary infertility. Average age of the patients was 29.14 years +5.65 SD with range 20-38 years. The deranged follicle stimulating hormone and deranged luteinizing hormone in IU/L among women presenting with an ovulatory cycle with primary infertility was observed in 85(59.44%) and 56(39.16%) respectively. Practical implication: This study will be useful to local health professionals in adjusting the management protocols for patients with primary infertility Conclusion: The deranged follicle stimulating hormone and deranged luteinizing hormone in IU/L are the considerable factors among women presenting with an ovulatory cycle with primary infertility Keywords: Follicle Stimulating Hormone, Luteinizing Hormone, An Ovulatory Cycle, Primary Infertility